Some Unconventional Thoughts on Understanding Behavior - Green, Thad B. (Academy of Management Journal, 1973)
The article discusses selfish behavior and the pursuit for personal payoffs among people. It explores how the concept of selfish behavior is associated with the concept that people pursue only pers...